Carbon Nanotube Areas - Printed on Textile and Paper Substrates - Arved C. Hubler; Lothar Kroll; Holg Elsner; Nora Wetzold; Thomas Fischer (Nanomaterials and Nanotechnology)
Mass printing processes are the key technology to produce mass products to the point of one-disposable. Carbon nanotube (CNT) based structures were prepared by flexographic printing using multi-walled carbon nanotube (MWCNT) dispersions in water. The carbon nanotubes were applied to a textile substrate made of polyester and polyamide microfilaments and to both-side coated paper to produce electrically conductive layers that can be used, for example, as heating elements. Carbon nanotube layers with sheet resistivity ranging from 0.12 to 3.00 kΩ/sq were obtained. The ratio of radiation power PS (determined according to the Stefan-Boltzmann law) of the printed layers to the electrical power spent, represents the efficiency of the system. The samples on textile substrate with a surface temperature of 169°C have an efficiency of 25%, the paper samples with a surface temperature of 93°C have an efficiency of about 15%.